2010
DOI: 10.1016/j.ecoenv.2010.08.035
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical effects and polycyclic aromatic hydrocarbons (PAHs) in senegal sole (Solea senegalensis) from a Huelva estuary (SW Spain)

Abstract: Relations between several stress oxidative biomarkers and aromatic polycyclic hydrocarbon (PAH) concentrations have been studied in wild sole, Solea senegalensis collected in the vicinity of a petrochemical industry. Antioxidant enzyme activities in eco-toxicological studies constitute excellent markers for exposure to a large variety of pollutants. The 16 PAHs in sediment as well as oxidative damage (LPO), activity of catalase (CAT), glutathione peroxidase (GPx), glutathione S-transferase (GST), glutathione r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(22 citation statements)
references
References 90 publications
1
21
0
Order By: Relevance
“…Biological indicators of habitat quality comprised responses at different levels of biological organization, namely sub-individual, individual and population level responses. In general, biological responses were within the range of values described in previous studies considering the same fish species (Fonseca et al, 2011a,b;Oliva et al, 2010;Vasconcelos et al, 2009). Looking into biological measures with higher specificity toward chemical stress, several biomarker responses to contaminants were integrated into a quality indicator, which showed a high correlation with habitat chemical contamination resulting in a similar habitat quality classification.…”
Section: Multiple Indicators Of Habitat Qualitymentioning
confidence: 87%
See 1 more Smart Citation
“…Biological indicators of habitat quality comprised responses at different levels of biological organization, namely sub-individual, individual and population level responses. In general, biological responses were within the range of values described in previous studies considering the same fish species (Fonseca et al, 2011a,b;Oliva et al, 2010;Vasconcelos et al, 2009). Looking into biological measures with higher specificity toward chemical stress, several biomarker responses to contaminants were integrated into a quality indicator, which showed a high correlation with habitat chemical contamination resulting in a similar habitat quality classification.…”
Section: Multiple Indicators Of Habitat Qualitymentioning
confidence: 87%
“…There is also a considerable amount of knowledge available considering this species distribution, ecological preferences, metabolic and biomarker responses to contamination, which grants essential baseline information for the present approach (e.g. Fonseca et al, 2006Fonseca et al, , 2010Oliva et al, 2010;Siscar et al, 2014;Solé et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Elevated GST activity may reflect the possibility of better protection against pesticide toxicity and used as biomarker for pollution monitoring (Ozcan Oruc 2010). Several studies reported GST activities to be significantly increased, but in most cases no significant differences were observed between fish from control and polluted sites (Pilarczyk and Correia 2009;Oliva et al 2010). Winston and Di Giulio (1991) found elevated rates of idiopathic lesions and neoplasia among fish inhabiting polluted environments to be related to the increased oxidative stress associated with pollutant exposure.…”
Section: Micronucleus Testmentioning
confidence: 99%
“…Although most of these studies relate to aquaculture, many environmental toxicological studies focusing on more classical biomarkers can be found, aiming at the fundamental mechanisms of exposure (for instance Chairi et al 2010;Kalman et al 2010) and at the biomonitoring of estuarine sediments (e.g. Riba 2004;Costa et al 2009a, b;Oliva et al 2010). In addition, some successful attempts using ''omic'' approaches can already been found, although most also relate to aquaculture, such as transcription analysis by cDNA microarrays and PCR techniques (Manchado et al 2008;Osuna-Jiménez et al 2009;Prieto-Á lamo et al 2009 and a few others) and proteomics (Forné et al 2009;Salas-Leiton et al 2009;Costa et al 2010).…”
Section: Introductionmentioning
confidence: 99%